Two novel diterpenes from the roots of Phyllanthus acidus (L.) Skeel. Issue 38 (21st September 2017) - Duong, Thuc-Huy; Bui, Xuan-Hao; Le Pogam, Pierre; Nguyen, Huu-Hung; Tran, Thi-Thuan; Nguyen, Thi-Anh-Tuyet; Chavasiri, Warinthorn; Boustie, Joël; Nguyen, Kim-Phi-Phung
Abstract: Two novel diterpenes, phyllanes A and B, were isolated from the roots of Phyllanthus acidus, along with the cleistanthane diterpene, spruceanol. Their chemical structures were unambiguously elucidated by extensive 1D and 2D NMR analyses and high resolution mass spectroscopic data, as well as by comparison with literature data. While phyllanes A and B are respectively reminiscent of amphilectane and serrulatane diterpenoids, their highly unusual substitution patterns and their co-occurrence with spruceanol led us to assume that they might correspond to an unprecedented type of re-arranged cleistanthane-diterpenoid precursors, resulting in final products that display a unique scaffold among terrestrial diterpenoids. Accordingly, a possible biosynthetic route to the two new compounds from the readily accessible spruceanol is proposed herein. These two compounds were evaluated for their cytotoxic activities against two cancer cell lines. Only phyllane B exerted a moderate activity against K562 and HepG2 cell line with IC50 values of 28.90 and 45.23 μg/mL, respectively. Graphical abstract: